The mystery of the Venus Island fetish [large type] - Flannery, Tim F. (Tim Fridtjof), 1956- (Thorndike Press large print mystery series., 2016)
Sydney, Australia, 1932. Recently returned from Venus Island, young anthropologist Archie Meek notices a strange discoloration on some of the skulls of the Great Venus Island Fetish. Has someone tampered with the ceremonial mask? The Mystery of the Venus Island Fetish is a delightfully risqué caper, full of eccentric characters, intrigue, and adventure.